2005
DOI: 10.1002/anie.200462704
|View full text |Cite
|
Sign up to set email alerts
|

Glory‐Scattering Measurement of Water–Noble‐Gas Interactions: The Birth of the Hydrogen Bond

Abstract: CommunicationsScattering cross sections for collisions of water and oxygen with the five noble gases reveal the onset of hydrogen bonds in water-noble-gas complexes, which increase in strength from He to Xe. Details on the determination of the strength of the interaction in excess of that expected for pure van der Waals forces are given by D. Cappelletti and co-workers on the following pages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
130
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 104 publications
(139 citation statements)
references
References 25 publications
8
130
1
Order By: Relevance
“…Moreover, the similarity between chargetransfer interaction and hydrogen bonding has been pointed out by many including Ratajczak and Orville-Thomas [50]. Quite recently, it has been shown that even Rg-H 2 O (Rg-rare gas) interactions show signs of hydrogen bonding [51], and not surprisingly charge-transfer interaction as well [52] for heavier noble gases such as Kr and Xe. Co-operativity and charge transfer are observed in most hydrogen-bonded systems, and they are included in the list of characteristics.…”
Section: Physical Forces Involved In the Hydrogen Bondmentioning
confidence: 84%
See 1 more Smart Citation
“…Moreover, the similarity between chargetransfer interaction and hydrogen bonding has been pointed out by many including Ratajczak and Orville-Thomas [50]. Quite recently, it has been shown that even Rg-H 2 O (Rg-rare gas) interactions show signs of hydrogen bonding [51], and not surprisingly charge-transfer interaction as well [52] for heavier noble gases such as Kr and Xe. Co-operativity and charge transfer are observed in most hydrogen-bonded systems, and they are included in the list of characteristics.…”
Section: Physical Forces Involved In the Hydrogen Bondmentioning
confidence: 84%
“…Results from molecular beam scattering experiments reported by Cappelletti and co-workers have shown that the RgؒؒؒH 2 O inter -action becomes "hydrogen bonding" as the rare gases become heavier [51], i.e., the HeؒؒؒH 2 O interaction is isotropic whereas the XeؒؒؒH 2 O interaction is very directional with the OHؒؒؒXe bond that is nearly linear. More recently, it has been shown that rare gas atoms cannot only be acceptors but also donors in hydrogen-bonded complexes.…”
Section: Hydrogen Bond Donors and Acceptorsmentioning
confidence: 99%
“…Glory structures in the total cross sections for H2O--rare gas collisions have also been investigated by the Perugia group. 15,16 Rotationally resolved state--to--state integral cross sections of ortho and para--H2O collisions with Ar were investigated by Chapman et al 13 They reported an approximate exponential--decay character of measured integral cross sections with the magnitude of rotational energy transfer of H2O. In addition to the energy gap model, a clear propensity of rotational excitation of H2O around the a and c principal axes was observed and compared with classical and quantum calculations.…”
Section: Introductionmentioning
confidence: 99%
“…As for other cases previously studied [8,[24][25][26][27][28], such an approach is useful to identify the intermolecular potential components that may add to the ubiquitous van der Waals interaction. For example, we recently reported [27,28] integration of the change in electron density occurring upon the formation of rare gaswater complexes (computed with accurate ab initio methods and basis sets), we mapped the local charge displacement along the whole intermolecular region and were thus able to appraise CT effects free of the inherent ambiguity of charge decomposition models [27,28].…”
Section: Introductionmentioning
confidence: 99%